Protecting Future Music Teachers from the Threat of “Public Culture” and Developing Their Social and Cultural Competence - Ashurov Mahmud Shaxobovich (International Journal on Integrated Education, 2021)
This article analyzes the development of socio-cultural competence to protect future music teachers from the threat of “popular culture”. The golden treasure of our people created over the centuries, national customs and traditions, rituals and values created in our rich history, the use of all the valuable riches of folk wisdom, including the development of modern personality, protection from the influence of popular culture. Opinions based on analyzes on the problem of issues in the field for the development of socio-cultural competence of the individual are covered.